2015
DOI: 10.1007/s00330-015-3987-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI in the early diagnosis of tubal ectopic pregnancy

Abstract: • MR imaging has served as a problem-solving procedure in ectopic pregnancy. • MR imaging features can be criteria for early diagnosis of tubal pregnancy. • Detailed assessment of ectopic implantation is necessary for management decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…In conclusion, our results show that in cases of inconclusive US, MRI can play an important role in the early diagnosis of extra-tubal pregnancy, providing accurate evaluation of the site and the possible infiltration of the lesion, which help the management of these patients [6].…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In conclusion, our results show that in cases of inconclusive US, MRI can play an important role in the early diagnosis of extra-tubal pregnancy, providing accurate evaluation of the site and the possible infiltration of the lesion, which help the management of these patients [6].…”
Section: Discussionmentioning
confidence: 66%
“…EP is a well-known acute condition, and is associated with a 9-14 % mortality rate [6]. The decision to institute medical therapy versus surgery requires accurate characterization of a suspected EP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon improper implantation of a fertilized egg in a fallopian tube, trophoblasts invade the wall of the fallopian tube to help form the placenta. This process causes hemorrhage to fill the lumen of the tube, leading to a distended tubular structure with signal characteristics of hemorrhage at various stages on MRI . In the setting of positive β‐hCG without an intrauterine gestational sac, the presence of unilateral hematosalpinx is highly concerning for an ectopic pregnancy, even without a demonstrable extrauterine gestation sac (Fig.…”
Section: Acute Gynecologic Conditions Related To Pregnancymentioning
confidence: 99%
“…5,6 With the development of diagnostic methods, precise diagnosis of interstitial pregnancy before rupture has become possible, which allows gynecologists to consider more conservative treatment. 7,8 Several cases had been reported that hysteroscopic management could be a feasible option with potentially less trauma to the interstitial uterine wall and less impact on subsequent pregnancy. [9][10][11][12][13] However, most of these reports are case reports.…”
Section: Introductionmentioning
confidence: 99%